Ida, always - Levis, Caron (Atheneum Books for Young Readers, 2016)
Gus lives in a big park in the middle of an even bigger city, and he spends his days with Ida. Ida is right there. Always. Then one sad day, Gus learns that Ida is very sick, and she isn't going to get better. The friends help each other face the difficult news with whispers, sniffles, cuddles, and even laughs. Slowly Gus realizes that even after Ida is gone, she will still be with him -- through the sounds of their city, and the memories that live in their favorite spots. (Based on the real Gus and Ida of New York's Central Park Zoo.).